SMEs, Growth, and Poverty - Beck, Thorsten; Demirgüç-Kunt, Asli (World Bank, Washington, DC, 2012)
This Note explores the relationship between the size of the small and medium-size enterprise (SME) sector and economic growth and poverty reduction. A new study finds no support for the widely held belief that SMEs promote higher growth and lower pover ty. But it does provide some support for the view that the quality of the business environment facing all firms, large and small, influences economic growth.